2(b-3)-2(3b-5)=4(3-b)

Simple and best practice solution for 2(b-3)-2(3b-5)=4(3-b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(b-3)-2(3b-5)=4(3-b) equation:


Simplifying
2(b + -3) + -2(3b + -5) = 4(3 + -1b)

Reorder the terms:
2(-3 + b) + -2(3b + -5) = 4(3 + -1b)
(-3 * 2 + b * 2) + -2(3b + -5) = 4(3 + -1b)
(-6 + 2b) + -2(3b + -5) = 4(3 + -1b)

Reorder the terms:
-6 + 2b + -2(-5 + 3b) = 4(3 + -1b)
-6 + 2b + (-5 * -2 + 3b * -2) = 4(3 + -1b)
-6 + 2b + (10 + -6b) = 4(3 + -1b)

Reorder the terms:
-6 + 10 + 2b + -6b = 4(3 + -1b)

Combine like terms: -6 + 10 = 4
4 + 2b + -6b = 4(3 + -1b)

Combine like terms: 2b + -6b = -4b
4 + -4b = 4(3 + -1b)
4 + -4b = (3 * 4 + -1b * 4)
4 + -4b = (12 + -4b)

Add '4b' to each side of the equation.
4 + -4b + 4b = 12 + -4b + 4b

Combine like terms: -4b + 4b = 0
4 + 0 = 12 + -4b + 4b
4 = 12 + -4b + 4b

Combine like terms: -4b + 4b = 0
4 = 12 + 0
4 = 12

Solving
4 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| .3*x=4 | | 3(2n+3)=9n-3+n-3 | | 0.3333x=4 | | =1 | | x^2+2x-45=0 | | 3(-3-3x)=-117 | | .2a=-4 | | X^2+24x+135=0 | | 0.3a=-3 | | x^2-y^2+y+x=0 | | 4x+2(3x-5)=2x+10 | | 15x-5=0 | | -5(9+2x)=-85 | | 12-(2x+5)=23-8x | | 6*5*4=y | | 8(x-20)=64 | | .5z+2=5 | | -5(x+1)=10(2x-1) | | 2x+5x-6=30 | | 3x+45-5*7=12 | | -x+3x+6x-2+6x= | | 4(x+2)=2x+20 | | 4(3+3x)-3=21 | | 3(2x+11)=41 | | x-22=10 | | 3(2x-5)=3 | | 2x=3.6 | | 3x-9=-21 | | 2(b-4)-6(b+8)=12(b+b)-8b+6 | | x-80=45+x | | x^2+2x-144=0 | | 24y-3=12y+1 |

Equations solver categories